Impact of histological thrombus composition on preinterventional thrombus migration in patients with acute occlusions of the middle cerebral artery. Issue 1 (February 2018) - Maegerlein, Christian; Friedrich, Benjamin; Berndt, Maria; Lucia, Kristin Elizabeth; Schirmer, Lucas; Poppert, Holger; Zimmer, Claus; Pelisek, Jaroslav; Boeckh-Behrens, Tobias; Kaesmacher, Johannes
Purpose: The occurrence of thrombus migration (TM) in middle cerebral arteries (MCAs) prior to mechanical thrombectomy (MT) in patients suffering from acute ischemic strokes is a crucial aspect as TM is associated with lower rates of complete reperfusion and worse clinical outcomes. In this study, we sought to clarify whether histological thrombus composition influences TM. Methods: We included 64 patients with acute MCA occlusions who had undergone MT. In 11 of the cases (17.2%) we identified TM prior to the interventions. The extracted clots were collected and histologically examined. The hematoxylin and eosin-stained specimens were quantitatively analyzed in terms of the relative fractions of the main constituents (red and white blood cells and fibrin/platelets). The histologic patterns were correlated with the occurrence of TM. Results: Patients in whom TM could be observed were more often treated in a drip-and-ship fashion (90.9% vs 41.5%, p  = 0.003). Stroke etiology did not differ between migrated and stable thrombi. A weak tendency for higher RBC and lower F/P content could be observed in thrombi that had migrated when compared with stable thrombi (RBC: median 41% vs 37%, p  = 0.022 and F/P: median 54% vs 57%, p  = 0.024). When using a cut-off of 60% RBC content for the definition of RBC-rich thrombi, a higher portion of RBC-rich thrombi could be identified in the migrated group as opposed to the stable group (36.4% vs 5.7%, p  = 0.003). Conclusion: Preinterventional TM may be influenced by the histological thrombus composition in a way that RBC-rich thrombi are more prone to migrate.